O efeito do processo terapêutico para problemas de fluência de fala no discurso de pais - Pires, Thais Inocêncio (2012)
Introduction: Speech fluency can be viewed as a complex event involving the organic, psychic and social dimensions. From this perspective, complaints about problems of speech fluency brought to the clinic by the family, call for the development of a therapeutic process that involves the entire family unit. Objective: To study, through the speech of parents, the effects and effectiveness of a therapeutic process for speech fluency problems based on a historical-dialectical approach. Method: qualitative research using semi-structured interviews with three families that have therapeutic work with the researcher. The interview began with the phrase: Tell me about your child's therapeutic process. The interviewer intervened to ensure that respondents talked about the vision they had about their children, his speech and the changes they observed. The transcribed interviews were categorized according to Bardin's Content Analysis (2009) in four categories: Therapeutic Approach; Experiences and Affections; Causes and Vision that Parents have about the Child, the Language and his Stuttering, the last one structured in three sub - categories: Feelings and Thoughts on Stuttering and Language; Social Situations and Characteristics of Communication. Results / Discussion: The therapeutic effects observed from the analysis of the categories were: in Therapeutic Approach parents reported that, unlike other approaches, whit the dialectical historical approach they felt part of the therapeutic process. In Experiences and Affections reports that speech moments before felt as harassed and helpless, came to be shared and seized as part of the process of speech production and that they understood that their feelings have an effect on the speech of the child. In Vision that Parents have about the Child, the Language and his Stuttering was reports about how the speech of their children was; about the changes observed; about the stigma they and their children carried and about their understanding that the social contexts intensified stuttering. Conclusion: These effects indicate that the therapeutic process supported on the historical dialectical approach was effective for the participants in this study. It also indicates that effectiveness is not only measured by the decrease in stuttering and disfluency of children, but mainly by change of attitude of parents toward this form of speech, which enabled such a decrease. This result points to the need and importance of further studies about this type of approach